Gen Z and Gen Alpha Algerian Youth and Digital Colonisabilité: A Bennabian Reading in the Age of the Algorithm - Sarnou, Dalal (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
This study examines how continuous exposure to global, mainly Western, digital content shapes the cultural identity and worldview of Algerian Generation Z and Generation Alpha. Drawing on Malek Bennabi’s concept of colonisabilité, it introduces the notion of digital colonisabilité to describe the growing susceptibility of individuals to cultural and ideological influences transmitted through global digital platforms. Postcolonial insights from Frantz Fanon, Gayatri Spivak, and Edward Said are also applied to analyze identity formation, representation, and symbolic dependency in digital environments. A mixed-methods approach was used, combining questionnaires, focus group discussions, and participant observation involving 65 Generation Z students (aged 20–24) from Abdelhamid Ibn Badis University and 30 Generation Alpha pupils (aged 10–14) from schools in Oran. Quantitative data were analyzed descriptively, while qualitative data were examined thematically. Findings show that both groups demonstrate strong digital literacy and linguistic adaptability. However, Generation Z displays hybrid identity negotiation, whereas Generation Alpha shows early signs of cultural assimilation. The study highlights the need to promote critical digital literacy and cultural autonomy among Algerian youth to navigate globalization with awareness and confidence.